Modeling and optimization of lead (II) adsorption by a novel peanut hull-g-methyl methacrylate biopolymer using response surface methodology (RSM) - Chaduka, Megnolia; Guyo, Upenyu; Zinyama, Ngceboyakwethu P.; Tshuma, Piwai; Matsinha, Leah C. (Taylor and Francis Inc., 2021)
The modeling and optimization of lead (II) adsorption was been characterized on a fabricated peanut hull-g-methyl methacrylate biopolymer. A graft copolymer from agro-based waste was prepared by copolymerizing activated carbon from peanut hulls and methyl methacrylate by the use of benzoyl peroxide as the radical initiator in the presence of an aluminum triflate cocatalyst. A central composite design (CCD) was employed to model batch adsorption experiments and optimize and characterize the influence and interaction of relevant parameters including the pH, contact time, adsorbent dosage, and initial concentration. The optimum conditions for the adsorption process were a pH of 5.7, a contact time of 63.75 min, an adsorbent dosage of 0.2250 g in 50 mL, and initial lead (II) concentration equal to 76.25 mg L 1 . Under these conditions, 99.30% of lead (II) was removed from aqueous solution. Isotherm studies demonstrated that the experimental results were in accordance with the Langmuir isotherm model with maximum adsorption capacities of 370.40 and 137.0 mg g 1 in the presence and absence of the cocatalyst, respectively. The experimental results concurred with a pseudo second-order kinetic model that described the adsorption process as chemisorptive. Consequently, the peanut hull-g-methyl methacrylate prepared in the presence of an aluminum triflate cocatalyst has been shown to be potentially effective and sustainable for the remediation of lead (II) from contaminated waters.